Yes‐associated protein regulates glutamate homeostasis through promoting the expression of excitatory amino acid transporter‐2 in astrocytes via β‐catenin signaling. Issue 5 (8th January 2023) - Xu, Xingxing; Wang, Jiaojiao; Du, Siyu; Shen, Xiya; Lian, Jiashu; Zhou, Jian; Wang, Mianxian; Feng, Wenjin; Lv, Zhaoting; Zhu, Junzhe; Jin, Lingting; Sun, Huankun; et al.
Abstract: The homeostasis of glutamate is mainly regulated by the excitatory amino acid transporters (EAATs), especially by EAAT2 in astrocytes. Excessive glutamate in the synaptic cleft caused by dysfunction or dysregulation of EAAT2 can lead to excitotoxicity, neuronal death and cognitive dysfunction. However, it remains unclear about the detailed regulation mechanism of expression and function of astrocytic EAAT2. In this study, first, we found increased neuronal death and impairment of cognitive function in YAP GFAP ‐CKO mice (conditionally knock out Yes‐associated protein [YAP] in astrocytes), and identified EAAT2 as a downstream target of YAP through RNA sequencing. Second, the expression of EAAT2 was decreased in cultured YAP −/− astrocytes and the hippocampus of YAP GFAP ‐CKO mice, and glutamate uptake was reduced in YAP −/− astrocytes, but increased in YAP‐upregulated astrocytes. Third, further investigation of the mechanism showed that the mRNA and protein levels of β‐catenin were decreased in YAP −/− astrocytes and increased in YAP‐upregulated astrocytes. Wnt3a activated YAP signaling and up‐regulated EAAT2 through β‐catenin. Furthermore, over‐expression or activation of β‐catenin partially restored the downregulation of EAAT2, the impairment of glutamate uptake, neuronal death and cognitive decline that caused by YAP deletion. Finally, activation of EAAT2 also rescued neuronal death and cognitive decline in YAP GFAP ‐CKO mice. Taken together, our study identifies an unrecognized role of YAP signaling in the regulation of glutamate homeostasis through the β‐catenin/EAAT2 pathway in astrocytes, which may provide novel insights into the pathogenesis of brain diseases that closely related to the dysfunction or dysregulation of EAAT2, and promote the development of clinical strategy. Main Points: Loss of YAP signaling in astrocytes causes neuronal excitotoxicity and disrupts glutamate homeostasis. EAAT2 and β‐catenin is down‐regulated in YAP‐/‐ astrocytes. Astrocytic YAP regulates glutamate homeostasis via the β‐catenin/EAAT2 signaling.